CONTEXTS OF COLONIALISM. Issue 2 (May 2016) - Smith, Woodruff D.
ABSTRACT: The contributions to the collection under review offer a wide range of treatments of ways in which German colonialism intersected with aspects of domestic German culture and politics, with particular attention to the larger global setting in which the German colonial empire existed between 1884 and 1918—or was remembered up to 1945. The review situates and critiques the contributions in interpretive contexts based on general suggestions by one of the editors, Geoff Eley. These include a context in which "colonialism" and "imperialism" are recognized as specific discursive constructions of the late nineteenth and early twentieth centuries, another in which the causal focus in interpreting colonial phenomena is placed on exchanges that constituted an accelerating globality with which available conceptual modes (including colonialism and imperialism) could not keep pace, a third that complicates the categorical distinctions usually made between types of imperial program, and a fourth that aims at replicating on a much broader and more flexible basis something like the concept of "social imperialism" that forty years ago dominated interpretations of German imperialism. The essay ends with a view of how such an interpretive framework might be constructed.